Longitudinal change in aphakic refraction after early surgery for congenital cataract - Nyström, Alf; Lundqvist, Kristina; Sjöstrand, Johan (Journal of AAPOS, 2010)
To characterize the longitudinal changes of refraction in aphakic eyes after early surgery for congenital cataract and to evaluate longitudinally measured aphakic refraction (individual vs group mean) as a noninvasive indicator of postoperative disturbances in ocular development. Records of children who had cataract surgery during their first year of life between 1980 and 1995 were obtained from a prospective, population-based study of congenital cataract. Only children with regular follow-up were included. Postoperative aphakic refraction was calculated at the corneal plane. Data were obtained up to 36 months of age. The study included 28 children (49 eyes) who underwent surgery at a median age of 2.8 months (range, 0-9 months). The decrease of aphakic refraction at the corneal plane followed a logarithmic trend ( R 2 = 0.95). A total of 36 eyes followed this pattern, with no growth in 8 eyes and an increased growth rate in 1 eye with uncontrolled glaucoma and 4 eyes of 2 children with Down syndrome. Most aphakic eyes follow a predictable, logarithmic change in refraction in the first 3 years of life, Longitudinal monitoring of refraction may prove to be a useful, noninvasive screening method for early detection of disturbances in aphakic eye growth.